Spotlight on faculty member Associate Professor Dr. Md Rezau Karim, biochemist - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
Dr. Md. Rezaul Karim was born in 1965, a third of six siblings comprising five brothers and one sister. His late father, Md. Bozlar Rahman was a school teacher and mother, Mrs. Haw a Bibi, a housewife. His father dreamt of getting all of them involved in the teaching profession, struggling with his small income to provide education for his children.